Cyber Corporate Social Responsibility Communication: Content Analysis on The Official Website of AQUA Group Company - Lenny Merantyca; Dini Salmiyah Fithrah Ali (Universitas Ahmad Dahlan, 2021)
The importance of extensive CSR communication is maintained to create a reputation and maintain long-term corporate sustainability. Thus, CSR communication needs to be maintained optimally and comprehensive in a sustainable way to help corporations increase its reputation in the stakeholder's perception and avoid the crisis. Development of cyber information technology makes it easier for stakeholders to gain access to CSR communication, including the use of official websites as accurate as CSR incomes. The study aims to find out how the CSR cyber-communications company AQUA Group activity through official websites. The study studied CSR message content analysis, CSR information presentation, and CSR communication patterns formed by AQUA Group through official websites. The study employed qualitative method of content analysis with a post positivism paradigm. Data collection was done with documentation study techniques that fit the research purposes. The results shows that the content of the CSR's cyber message has been communicated not to refer to the principle of transparency to the content of the internal group's message on employment issues. The CSR's cyber information presentation suggests the AQUA Group has a high level of interactivity on the information fulfillments facility, but it has a low rate of accessibility. The CSR's cyber communication pattern that AQUA Group used a symmetrical two-way communication pattern (the two way symmetrical) by building on stakeholder relationships.